The efficacy of single dose ivermectin in the treatment of hookworm related cutaneous larva migrans varies depending on the clinical presentation. (1st February 2013) - Vanhaecke, C.; Perignon, A.; Monsel, G.; Regnier, S.; Bricaire, F.; Caumes, E.
Abstract Background Treatment of hookworm‐related cutaneous larva migrans (HrCLM) with a single dose of oral ivermectin has not been adequately evaluated to date. Response rates reported in three large studies varied from 77% to more than 95%. Objectives We evaluated the efficacy of ivermectin in the treatment of HrCLM. Methods We retrospectively studied all returning travellers with HrCLM who consulted in our institution. Patients were then treated with a single, 200 μg/kg dose of ivermectin, orally. Results Sixty‐two travellers (35 female, 27 male, mean age 35.6 years) with HrCLM and creeping dermatitis were included. Six patients (10%) also had associated hookworm folliculitis. Fifty‐nine patients (95%) completely responded with one ivermectin dose. The response rate was 98% in the 56 patients presenting with only creeping dermatitis and 66% in the six patients presenting with additional hookworm folliculitis (P = 0.02). Conclusion The efficacy of a single dose of oral ivermectin is higher in patients with only creeping dermatitis than in those with associated hookworm folliculitis.